Eternal Facts in an Ageing Universe - Correia, Fabrice; Rosenkranz, Sven (My University, 2012)
In recent publications, Kit Fine devises a classification of A-theories of time and defends a non-standard A-theory he calls fragmentalism, according to which reality as a whole is incoherent but fragments into classes of mutually coherent tensed facts. We argue that Fine's classification in not exhaustive, as it ignores another non-standard A-theory we dub dynamic absolutism, according to which there are tensed facts that stay numerically the same and yet undergo qualitative changes as time goes by. We expound this theory in some detail and argue that it is a serious alternative to the positions identified by Fine.